Systems-Centered Practice : Selected Papers on Group Psychotherapy. - Agazarian, Yvonne (Karnac Books, 2006)
The author has developed a theory of Living Human Systems and its systems-centered practice. This book presents a series of chapters that trace the development of the theory of Living Human Systems through the years of 1987 to 2002. As the theory develops, so do the methods and techniques that put it into practice. The last chapter summarizes the current application and the nuts and bolts of systems-centered therapy.